2010
DOI: 10.14411/fp.2010.015
|View full text |Cite
|
Sign up to set email alerts
|

The role of latent toxoplasmosis in the aetiopathogenesis of schizophrenia - the risk factor or an indication of a contact with cat?

Abstract: Abstract:We assessed igg antibody to Toxoplasma gondii in 300 inpatients with schizophrenia (SG), 150 outpatients with anxiety and depressive disorders (PCG), and 150 healthy blood donors (HCG). Seropositivity rates were 60.7% for SG, 36.7% for PCG, and 45.3% for HCG (p<0.001). The seropositivity rate for anti-Toxoplasma IgG antibodies in SG was significantly higher that in PCG (X 2 = 23.11, OR = 2.66, p = 0.001) and HCG (X 2 = 9.52, OR = 1.86, p = 0.002). Among SG, 85% of those who reported close cat contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 49 publications
3
32
2
2
Order By: Relevance
“…The present finding is in contrast with the studies conducted by Alvarado-Esquivel et al [49], Yuksel [50], and Xiao et al [37], which demonstrated that seroprevalence of anti- T. gondii IgG is not different between men and women with schizophrenia disorder. On the other hand, Lindová et al [51] reported higher seropositivity in male than in female schizophrenic patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The present finding is in contrast with the studies conducted by Alvarado-Esquivel et al [49], Yuksel [50], and Xiao et al [37], which demonstrated that seroprevalence of anti- T. gondii IgG is not different between men and women with schizophrenia disorder. On the other hand, Lindová et al [51] reported higher seropositivity in male than in female schizophrenic patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar results were also reported in numerous studies. 2,17 By contrast, higher seropositivity in schizophrenic women than in schizophrenic man was also indicated by Khademvatan et al 14 In the present study, seroprevalence of T. gondii was not significantly different between the schizophrenia group and healthy controls with respect to age groups. However, the OR was detected as 3.5 in the >50-year age group.…”
Section: Discussionsupporting
confidence: 60%
“…1 By contrast, epidemiologic studies have indicated that environmental exposures, such as winterespring birth, urban birth, and peri-and postnatal infections, are risk factors for the disease developing in later life. 2 In researches on infectious agents, it has been hypothesized that Toxoplasma gondii is a potentially relevant etiological factor in some cases of schizophrenia. 3e5 T. gondii that commonly infects humans and animals is an obligate intracellular protozoan parasite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in many previous studies, the infection sources are consumption of contaminated raw meat [2], water [3], fruits [4] and vegetables [5] or having close contacts with felines [6] and exposure to soil contaminated with cats' feces [7]. Infection during early pregnancy is more serious compared to infection in late gestation, but the likelihood of disease transmission increases during the progression of pregnancy [8].…”
Section: Introductionmentioning
confidence: 99%